2017
DOI: 10.1038/s41598-017-01685-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine profiles of interstitial pneumonia in patients with dermatomyositis: a case control study

Abstract: Chemokines play an important role in the pathophysiology of dermatomyositis (DM) with interstitial pneumonia (IP). However, the relation between chemokines and the disease activity or prognosis of DM-IP has not been elucidated. We evaluated the serum C-C motif chemokine ligand (CCL) 2, Th1 chemokines (C-X-C motif chemokine ligand [CXCL] 9, CXCL10, CXCL11), and Th2 chemokine (CCL17) profiles of 30 patients, and examined the relation between these chemokines and the disease activity or prognosis of DM-IP. Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…In addition, we showed that patients with CVD–ILD and IPAF treated with immunosuppressants had higher pre-treatment serum levels of CXCL9 and CXCL11 and greater improvements in annual FVC after treatment. Studies have also suggested associations between the disease activity of autoimmune diseases and serum or BALF CXCL9, CXCL10, and CXCL11 levels in patients with SLE, DM, or SScs [ 7 , 20 , 24 , 25 ]. However, the clinical management of CVD–ILD and IPAF remains difficult due to a lack of accurate diagnosis, disease activity, and therapeutic response markers [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that patients with CVD–ILD and IPAF treated with immunosuppressants had higher pre-treatment serum levels of CXCL9 and CXCL11 and greater improvements in annual FVC after treatment. Studies have also suggested associations between the disease activity of autoimmune diseases and serum or BALF CXCL9, CXCL10, and CXCL11 levels in patients with SLE, DM, or SScs [ 7 , 20 , 24 , 25 ]. However, the clinical management of CVD–ILD and IPAF remains difficult due to a lack of accurate diagnosis, disease activity, and therapeutic response markers [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum amyloid A-3 (SAA3) is an acute phase response protein whose transcription is strongly induced by endotoxin-induced lung inflammation [ 28 ]. Chemokine ligand 9 (CXCL9) is a small cytokine belonging to the CXC chemokine family, which is induced by inflammatory responses and is also known to be induced by pulmonary inflammation [ 29 ]. Orm1 is a gene encoding the orosomucoid 1 (ORM1) protein, which is classified as an acute phase protein and is increased by an acute inflammatory reaction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 has been shown to be associated with survival (the serum CCL2 level is higher in nonsurvivors in ILD-DM) [98]. In this study by Oda et al, the survival rate after 52 weeks was significantly lower in patients with a level of CCL2 of ≥900 pg/mL than in those with <900 pg/mL; serum CCL2 levels were significantly higher in the nonsurvivors than in the survival group.…”
Section: Resultsmentioning
confidence: 64%
“…A positive correlation was found between CXCL10 and with the global VAS score [63, 65] and the pulmonary VAS but not with ferritin level [65]. Interestingly, CXCL10 could be used as a prognosis marker as levels at 2 weeks after treatment initiation were significantly higher in nonsurvivors [98]. However, serum CXCL10 level was not different between survivors and nonsurvivors in ILD-DM [98] and between RP-ILD and C-ILD [65].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation